A benchtop induction-based AC magnetometer for a fast characterization of magnetic nanoparticles. (1st June 2022) - Saari, Mohd Mawardi; Sulaiman, Mohd Herwan; Ahmad, Hamzah; Lah, Nurul Akmal Che; Sakai, Kenji; Kiwa, Toshihiko; Tsukada, Keiji
Abstract: In this study, we report a development of a benchtop induction-based AC magnetometer to realize a simple, wideband, and sensitive AC magnetometer for bio-sensing applications and characterization of magnetic nanoparticles (MNPs). We investigate the inductance and parasitic capacitance of six different pickup coil geometries and compare their sensitivity and usable frequency range. In the pickup coil design, the number of turns and coil section separation are varied from 200 to 400 turns, and 1 to 4 sections, respectively. We find that the usable frequency range is greatly affected by the pickup coil's inductance due to the self-resonance phenomena compared to their parasitic capacitance. A low noise instrument amplifier circuit (AD8429, Analog Devices, USA) was integrated and fabricated on a printed circuit board to amplify the weak signal from the pickup coil. We also implement a generalized Goertzel algorithm to achieve fast signal amplitude and phase extractions at a frequency. The developed magnetometer shows a sensitivity of 10 −8 Am 2 /√Hz at 6 Hz and a frequency range of up to 158 kHz. Using the developed AC magnetometer, we demonstrate the viscosity effect on the frequency response of thermally blocked, single-core nanoparticles (SHP30, Ocean Nanotech, USA) in glycerol solutions. The excitation frequency is swept from 5 Hz to 158 kHz at a field amplitude of 0.55 mTpp within the acquisition time of 5 min (51 points). As a result, the viscosity change is confirmed by the peak shifting in the imaginary magnetization curve towards lower frequency values when the wt/V% of the glycerol solution is increased. The hydrodynamic size and the average anisotropy energy ratio σ are estimated to be 60.6 nm and 25, respectively, from the complex AC magnetization. It can be expected that the developed AC magnetometer can be a valuable tool in providing a fast and reliable assessment of MNPs for bio-sensing applications.